Pengembangan Modul Ajar Fisika Berbasis Problem Based Learning Untuk Peserta Didik Fase E - Yusdarina, Yusdarina; Agussalim, Agussalim; Napsawati, Napsawati; Idamayanti, Reski; Basri, Syamsuriana (Journal of Health, Education, Economics, Science, and Technology, 2025)
The purpose of this study is to design a problem-based physics learning module (PBL) for phase E students on measurement material. This study is a research and development (R&D) that refers to the ADDIE development model. The five stages of the model are analysis, design, development, implementation, and evaluation. The validation sheet from the learning device expert serves as an instrument for this study, which is limited to the implementation stage. Based on the results of expert validation, the developed learning module is categorized as very feasible with a percentage of 86% and is stated to be usable in the learning process, especially in physics subjects on measurement material.